REGULATION AND PROTECTION OF CONSUMER PERSONALITY RIGHTS (Revista Paradigma, 2023)
The fact of the Federal Constitution in its art. 173, delimiting the State's performance in the market, does not mean its total removal from the economic field, especially in the capitalist model in a democratic State of law. Based on this premise, there will be a presentation of the characteristics of the regulatory agencies, their usefulness and their main issues (advantages and disadvantages), an analysis of the problems to culminate, indicating some solutions. Using the hypothetical deductive method, the importance of free competition and, in particular, of protecting the rights of the economic agents involved will become evident. Considering the context in which regulatory agencies are inserted (even in times of pandemic), there will be a focus on the role attributed to them to act to have balanced, harmonious and constructive markets, especially regarding the protection of consumer rights. In this sense, special attention will be paid to the provision of certain regulated services, such as water, electricity and health, which make up an existential minimum, since they are essential to life (health such as physical and mental integrity). Finally, rights inherent to personality and human dignity.